Bradykinin Sequestration by Plasmodium berghei Infected Erythrocytes Conditions B2R Signaling and Parasite Uptake by Fetal Trophoblasts - de Moraes, Luciana Vieira; Barateiro, André; Sousa, Patrícia Marques; Penha-Gonçalves, Carlos (Frontiers in Microbiology, 2018)
Plasmodium infection during pregnancy causes placental malfunction reducing fetus sustainability and leading to abortions, stillbirths, low birth weight or premature delivery. Accumulation of infected erythrocytes in the placenta is a key factor in placental malaria pathogenesis but the role played by fetal trophoblast cells that contact maternal blood has been neglected. Here we explore the hypothesis that interactions between Plasmodium-infected erythrocytes (IE) and fetal trophoblast cells impact on vasoactive alterations underlying placental dysfunction. We screened gene expression of key mediators in vasoactive pathways. We found that mRNA of bradykinin receptor 2 (B2R) and nitric oxide synthase (eNOS), as well as levels of bradykinin (BK), were decreased in late gestation placentas of pregnant P. berghei-infected mice. Co-culturing mouse trophoblasts with IE down-regulated B2R transcription and IL-6 secretion in a B2R-signaling dependent manner. IE showed increased levels of surface B2R and enhanced capacity to bind BK. We propose that down-regulation of B2R signaling in the course of IE-trophoblast interactions is due to BK sequestration by IE. In corroboration, levels of BK were lower in infected placentas and the positive correlation of B2R gene expression and fetal weight was disrupted by infection. This indicates that deregulation of the BK-B2R pathway is associated to placental dysfunction provoked by malaria infection. We further found that upon inhibition of B2R signaling, trophoblasts engulf IE to a lesser extent and show reduced production of IL-6. Our data suggest that BK sequestration by P. berghei represents a strategy for the parasite to ameliorate the risk of phagocytic capture by down modulating B2R activation.